2017
DOI: 10.1111/head.13146
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Migraine and the Most Common Psychiatric Co‐Morbidities

Abstract: This review examines the recent literature investigating the associations between migraine and the most common psychiatric co-morbidities. Also discussed are implications for treating individuals with co-morbid migraine and psychiatric disorders, including recent innovations and improvements for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 52 publications
0
30
0
1
Order By: Relevance
“…While no CTh studies have been conducted to explore headache phase-related cortical plasticity in migraine. An extensive literature has shown that a wide range of psychiatric disorders, especially anxiety and depression, can accompany migraine [4,[47][48][49]. Previous studies revealed cortical abnormalities in depression [35,50,51] and anxiety disorders [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…While no CTh studies have been conducted to explore headache phase-related cortical plasticity in migraine. An extensive literature has shown that a wide range of psychiatric disorders, especially anxiety and depression, can accompany migraine [4,[47][48][49]. Previous studies revealed cortical abnormalities in depression [35,50,51] and anxiety disorders [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…73 Further study is needed of the behavioral and pharmacological insomnia therapies, but to date only the behavioral approach improved headache. Psychiatric Comorbidity.-Psychiatric disorders are comorbid with both headache 74,75 and sleep disorders. [76][77][78] Insomnia and/or daytime sleepiness are symptoms of mood and anxiety disorders as well as chemical dependencies.…”
Section: Assess Sleep Disturbance and Insomnia In Chronicmentioning
confidence: 99%
“…However, a direct comparison to previous work is quite difficult, since only a few recent studies investigated a variety of comorbidities . Thus, the most well‐known concomitant disease of patients suffering from migraine is the psychological/psychiatric disorder, which has been supported by a large body of evidence of clinical and population‐based studies . A representative US study conducted by Breslau and his colleagues showed a threefold higher lifetime prevalence of major depression in persons with migraine or severe headache, compared with the healthy control group .…”
Section: Discussionmentioning
confidence: 99%
“…35 Thus, the most well-known concomitant disease of patients suffering from migraine is the psychological/psychiatric disorder, which has been supported by a large body of evidence of clinical and population-based studies. 17,20,36,37 A representative US study conducted by Breslau and his colleagues showed a threefold higher lifetime prevalence of major depression in persons with migraine or severe headache, compared with the healthy control group. 38 Similar to our finding the authors estimated that about 41% of those patients with migraine were diagnosed with major depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation